2018
DOI: 10.1177/0093854818774386
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Evaluation of the Supervision With Immediate Enforcement Probation Program for Adult Gang–Affiliated Offenders in Texas

Abstract: As of 2012, it was estimated that there were more than 30,000 active gangs in the United States with at least 850,000 members. Despite significant challenges that criminal justice agencies and personnel face in treating and supervising gang members, few studies have examined adult gang member outcomes and the effects of community supervision on gang-affiliated offenders. Recent research demonstrates mixed evidence that high-risk offenders have better outcomes in smaller problem-solving courts and programs, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For example, Boxer and colleagues (2015) found that gang involvement reduced the likelihood of successful outcomes, and Saunders and colleagues (2009) found that gang members were much more likely to recidivate. However, other research has indicated that gang labels and technical violations—rather than new charges—are factors that can increase the risk of recidivism (Boots et al, 2018; Rios, 2011). Given that community corrections nationally have been supervising people connected with gangs for over 30 years, there is a substantial need to understand the specific factors that help people successfully transition out of gangs and off supervision.…”
Section: Gangs and Recidivismmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Boxer and colleagues (2015) found that gang involvement reduced the likelihood of successful outcomes, and Saunders and colleagues (2009) found that gang members were much more likely to recidivate. However, other research has indicated that gang labels and technical violations—rather than new charges—are factors that can increase the risk of recidivism (Boots et al, 2018; Rios, 2011). Given that community corrections nationally have been supervising people connected with gangs for over 30 years, there is a substantial need to understand the specific factors that help people successfully transition out of gangs and off supervision.…”
Section: Gangs and Recidivismmentioning
confidence: 99%
“…Carefully crafting and implementing effective supervision strategies is even more critical for gang-involved youth and adults who, as discussed above, face intense challenges with respect to desistance (Boots et al, 2018; Matz et al, 2014; Spooner et al, 2017; Trulson et al, 2012). The precise mechanisms leading to recidivism, and how to prevent its occurrence, require more thorough research to address the needs of this high-risk population.…”
Section: Gangs and Recidivismmentioning
confidence: 99%